A heterodinuclear, formal Au+IPt0 complex with weakly bound alkene ligands. Issue 40 (22nd April 2020) - Ernst, Lukas D.; Koessler, Konstantin; Peter, Andreas; Kratzert, Daniel; Scherer, Harald; Butschke, Burkhard
Abstract : Due to the weakly bound alkene ligands, [(Ph3 P)AuPt(nbe)3 ][BAr4 F ] can serve as a precursor for the synthesis of formal Au +I Pt 0 complexes. Abstract : [(Ph3 P)AuPt(nbe)3 ][BAr4 F ] (nbe = norbornene) constitutes the first olefin-containing, formal Au +I Pt 0 complex. The unusual coordination mode and the electronic properties have been analyzed spectroscopically and by calculations. The low binding energy of the nbe ligands make this complex a valuable precursor for formal Au +I Pt 0 complexes and a candidate for heterobimetallic catalysis.